Validation of a peridynamic model for fatigue cracking. (August 2016) - Zhang, Guanfeng; Le, Quang; Loghin, Adrian; Subramaniyan, Arun; Bobaru, Florin
Highlights: Peridynamic fatigue cracking model with improved stability and efficiency. Convergence studies in terms of fatigue crack path and fatigue life. Validation against experimental results for a curved fatigue crack path. Peridynamic model predicts sensitivity of crack path to location of added hole in sample. Simulation of fatigue crack nucleation, growth, and final failure in a two-phase composite. Abstract: Fatigue cracking in homogeneous and in composite materials is studied using a peridynamic model. We introduce a set of critical damage factors that improve stability and efficiency of a recently introduced peridynamic model for fatigue cracking. We perform convergence studies in terms of the nonlocal region size for a modified compact tension test which leads to curved fatigue crack paths. The experimental crack paths are strongly influenced by the location of a hole in the specimen, and the peridynamic results capture this sensitivity well. Fatigue lifetimes obtained by the peridynamic model are in good agreement with experiments for different crack growth rates in different cycle ranges. Different from methods based on classical continuum mechanics, the peridynamic fatigue crack model does not require additional criteria to guide crack or damage growth. In particular, we use the peridynamic fatigue model, without any modifications, to simulate fatigue crack growth in a two-phase composite in which several crack initiation points exist and where fatigue crack paths interact in complex ways.